Understanding the influence of Tween 80 on pullulan fermentation by Aureobasidium pullulans CGMCC1234. (20th January 2016) - Sheng, Long; Tang, Guiyue; Su, Peng; Zhang, Jinling; Xiao, Qian; Tong, Qunyi; Ma, Meihu
Highlights: The maximum pullulan yield increased 41% with the presence of Tween 80. The dispersed filaments were not easily entangled and less pellets were formed. FT-IR spectrum analysis indicated that the evaluated sample was pullulan. The molecular weight of sample significantly dropped comparing with the control. Abstract: In this paper, several new perspectives concerned with the effect of Tween 80 promoting pullulan production were presented. With the presence of Tween 80, the maximum pullulan yield increased by 41% (53.04 g/L). Meanwhile, the carbon source was consumed faster and the broth viscosity was higher. The lower final pH suggested that Tween 80 could protect the integrity of the mycelia. The dispersed filaments were not easily entangled with each other and less pellets were formed in the Tween 80 culture broth. FT-IR spectrum analysis indicated that the evaluated sample structure was coincided with commercial pullulan. The molecular weight of sample significantly dropped comparing with the control. The above findings indicated that Tween 80 facilitated the uptake of nutrient from surroundings to the microorganism and the release of pullulan into the extracellular fluid. These results were useful in better understanding the regulation and optimization of efficient pullulan fermentation.